ANALISIS PEMBELAJARAN BERDIFERENSIASI MELALUI PENDEKATAN STEAM (SCIENCE, TECHNOLOGY, ENGINEERING, ART, MATHEMATIC) PADA KEMAMPUAN LITERASI NUMERASI SISWA KELAS III SEKOLAH DASAR NEGERI 02 JATIYOSO TAHUN AJARAN 2024/2025 - Laela Cahyu Andini; Dwi Anggraeni Siwi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Analysis of Differentiated Learning through the STEAM (Science, Technology, Engineering, Art, Mathematic) Approach on the Numeracy Literacy Skills of Grade III Students of State Elementary School 02 Jatiyoso in the 2024/2025 Academic Year. The purpose of this study is to analyze the application of STEAM differentiated learning, in relation to the numeracy literacy skills. This research is a qualitative case study type, allowing researchers to investigate or analyze a phenomenon comprehensively, intensively, in detail, and in depth, the research phenomenon is still holistic, complex, and dynamic. Through qualitative research methods, researchers will analyze differentiated learning through the STEAM approach which will be linked to how the numeracy literacy skills. The results of the study indicate that the application of differentiated learning through the STEAM approach provides good learning for the numeracy literacy skills. This finding was obtained through triangulation of data that had been processed by researchers through observation, interviews, documentation, and tests consisting of 2 types of tests, namely formative evaluation in the form of the Mathematics Problem Solving Test (TPMM) and the Project Problem Solving Test (TPSP) which showed progress in the ability to read story problems, identify important information, and solve mathematical problems based on real contexts. This is in accordance with the approach used, namely STEAM which is centered on projects based on real-world problems, and is a multidisciplinary learning approach that is integrated to foster and improve the realization of the objectives of the independent learning curriculum designed according to 21st century skills.